Effect of NaNbO3crystals on the electrical properties of Na0.47K0.47Li0.06NbO3ceramics synthesised by seed induced method - Chavalit Suksri (2018)
Copyright © 2016 American Scientific Publishers All rights reserved. In this work, we investigated the influence of crystalline NaNbO3on the electrical properties of Na0.47K0.47Li0.06NbO3(NKLN) ceramics. Preparation by the conventional method for the upcoming phase of random elements did not control the properties. For this reason, we studied the electrical properties and phase formation that occurred with the addition of NaNbO3crystals, used at the initial phase of the reaction, in order to modify the electrical properties of NKLN ceramics. We synthesized lead-free piezoelectric ceramics by the seed-induced method. We prepared the NaNbO3crystals used as seeds by molten salt synthesis (MSS). We mixed the powder oxides of Na2CO3and Nb2O5with NaCl oxides-salt ratio 1:6. The seeds varied in content from 0 to 20 mol%. The calcination temperature of NKLN was from 800 to 900°C for 10 h, using two-step sintering (TSS) techniques. Our investigation further reported on the microstructure and the electrical properties. The results showed high Curie temperature of about 480°C, while the effect of the seed crystal improved the piezoelectric properties of the samples, compared with the conventional mixed-oxide.